Political Communication in Community Participation: A Systematic Literature Review - Titis Ayu Angganten; Salahudin; Muhammad Firdaus (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2024)
The purpose of this study is to see how communication affects the political participation of rural communities. This research uses a systematic literature review method using 219 scholarly articles from the Scopus database. The review of the articles was conducted using the Vosviewer application. The results revealed that there are 5 thematic clusters in the study of political communication participation, including the green cluster, yellow cluster, purple cluster, red cluster, and blue cluster. Where each cluster has a strong relationship between clusters. The politics of local leaders affect all aspects of community life in the area. Good leaders are developed through a long process and do not appear by chance. The ability to get others to do what the leader wants is known as leadership.  Communication in the community is considered to work well in the process of political participation in the community, despite the poorly understood and inadequate form of information distribution. The process of political participation in the election of leaders and other political bodies runs smoothly with the support of available communication media. Villagers are invited to participate in decision-making because they better understand what is needed for the welfare of the village. The results of this research help people's political participation in various ways and provide information to people who need it. The research process was limited because the articles used were only from the Scopus database, so the research results could not cover the issue of government communication in increasing the participation of rural communities as a whole.  Future research should use scientific article sources from recognized international databases such as Web of Science and Dimensions Scholars, so this research itself has weaknesses that need to be improved for future research.